AKTIVITAS Fusarium oxysporum DALAM MENGHIDROLISIS ECENG GONDOK (Eichhornia crassipes) DENGAN VARIASI WAKTU FERMENTASI - Tristianti, Siska Yulyana (Chem Info Journal, 2013)
Fusarium oxysporum activity to hydrolyze water hyacinth (Eichhornia crassipes) with variations of fermentation time taken to get the Fusarium oxysporum that have adapted to the fermentation medium of water hyacinth (Eichhornia crassipes) and obtain activity data of Fusarium oxysporum in hydrolyzing water hyacinth (Eichhornia crassipes) on variations of fermentation time. Activities Fusarium oxysporum based on the ability to hydrolyze water hyacinth mass accretion based cell (dry weight) produced. This research found that Fusarium oxysporum capable of growing on water hyacinth fermentation media and the activity of Fusarium oxysporum to hydrolyze water hyacinth occurred at optimum fermentation time at hours-168 which is the exponential phase of Fusarium oxysporum.